Improving Bali Cattle Productivity Through the Application of Combination Feeding "Healthy Herbs and Probiotics" in Feed for Cattle Farmers At DLT-UNJA Pudak Village, Kumpeh Ulu Subdistrict Muaro Jambi Regency (Journal of Saintech Transfer, 2023)
Currently, the level of knowledge among cattle farmers in raising cattle is still low, as evidenced by the conventional nature of the farming system, resulting in low productivity. The optimal utilization of appropriate technology to improve the productivity of cattle has not been achieved. The community service activities conducted involve technology transfer to enhance innovation and creativity among farmers through the application of herbal medicine and probiotics in the provided feed. The technology is implemented using the "Learning By Doing" method to ensure that innovation can be directly conveyed and easily understood by the farmers. The application of herbal medicine and probiotics in cattle feed is carried out directly for approximately 1.5 months, with cattle being weighed every 15 days. The results of this activity indicate that the implementation of appropriate technology through the use of herbal medicine and probiotics in cattle feed among a group of cattle farmers in DLT-UNJA, Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency, has increased the productivity of Bali cattle with a body weight gain of 0.59 kg/head/day.